Kinerja Lalu Lintas dan Persepsi Pengguna Jalan terhadap Keselamatan Berkendara di Simpang Tak Bersinyal (Studi Kasus: Simpang KB dan Peunaga di Kota Meulaboh Kabupaten Aceh Barat, Indonesia) - Hilma Erliana; Ferdiansyah Novriza; Enny Irmawati Hasan (Jurnal Teknik Sipil, 2026)
The city of Meulaboh, as the centre of activity in West Aceh Regency, Indonesia, has experienced an increase in traffic volume, making unsignalled intersections prone to accidents, driven by conflicts of priority and low driving discipline. This vulnerability is triggered by conflicts of priority and low driving discipline. This study aims to analyse the performance of both intersections through a hybrid approach that integrates technical analysis based on PKJI 2023 with a road user perception survey. Technically, it analyses capacity (q), degree of saturation (DJ), and level of service (LOS). Socially, it examines driver behaviour, accessibility, and the effectiveness of law enforcement. Data was collected through field surveys to measure traffic volume and questionnaires distributed to a number of respondents to obtain perception and preference data. The results show that traffic flow (q) reached 1543.8 SMP/hour (KB Intersection) and 1664.6 SMP/hour (Peunaga Intersection), saturation degree (DJ) 0.52 and 0.61, and level of service (LOS) C, indicating near-saturated conditions. On the other hand, the road user perception survey revealed that 82% of respondents acknowledged that traffic violations were a common sight. Meanwhile, 76% of respondents assessed that law enforcement in the intersection area was still weak and suboptimal. The simultaneous implementation of PKJI 2023 and a social approach reveals that traffic overcapacity is not only caused by technical factors, but is also exacerbated by driver behaviour and weak enforcement of regulations. Therefore, it can be concluded that improvement efforts require an approach that combines infrastructure interventions with increased driving discipline and consistent law enforcement to achieve a sustainable transport system in the city of Meulaboh, West Aceh Regency, Indonesia.